Pengaruh Pelatihan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Unit Usaha Pabrik Kelapa Sawit Pinang Tinggi PT Perkebunan Nusantara VI Jambi - Nur Rizkiroh Septiani; Nurhidayah Nurhidayah; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine the effect of training, motivation and work discipline on employee performance in PKS Pinang Tinggi business unit PT Perkebunan Nusantara VI Jambi. This research includes a type of research with quantitative. The method used is multiple linear regression. The sampling technique uses the formula from Solvin with the calculation results of 60 samples. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously. Variable Training (X1), Motivation (X2), has a significant effect on Employee Performance (Y). And there is a partial influence between Training (X1), Motivation (X2), which has a significant effect on Employee Performance (Y). Keywords: Training, Motivation, has a significant effect on Employee Performance